High dose-rate brachytherapy of localized prostate cancer converts tumors from cold to hot. Issue 1 (24th June 2020) - Keam, Simon P; Halse, Heloise; Nguyen, Thu; Wang, Minyu; Van Kooten Losio, Nicolas; Mitchell, Catherine; Caramia, Franco; Byrne, David J; Haupt, Sue; Ryland, Georgina; Darcy, Phillip K; Sandhu, Shahneen; et al.
Abstract : Background: Prostate cancer (PCa) has a profoundly immunosuppressive microenvironment and is commonly immune excluded with few infiltrative lymphocytes and low levels of immune activation. High-dose radiation has been demonstrated to stimulate the immune system in various human solid tumors. We hypothesized that localized radiation therapy, in the form of high dose-rate brachytherapy (HDRBT), would overcome immune suppression in PCa. Methods: To investigate whether HDRBT altered prostate immune context, we analyzed preradiation versus postradiation human tissue from a cohort of 24 patients with localized PCa that received HDRBT as primary treatment (RadBank cohort). We performed Nanostring immune gene expression profiling, digital spatial profiling, and high-throughput immune cell multiplex immunohistochemistry analysis. We also resolved tumor and nontumor zones in spatial and bioinformatic analyses to explore the immunological response. Results: Nanostring immune profiling revealed numerous immune checkpoint molecules (eg, B7-H3, CTLA4, PDL1, and PDL2) and TGFβ levels were increased in response to HDRBT. We used a published 16-gene tumor inflammation signature (TIS) to divide tumors into distinct immune activation states (high: hot, intermediate and low: cold ) and showed that most localized PCa are cold tumors pre-HDRBT. Crucially, HDRBT converted 80% of these 'cold'-phenotype tumors into an 'intermediate' or 'hot' class. We used digital spatial profiling to show these HDRBT-induced changes in prostate TIS scores were derived from the nontumor regions. Furthermore, these changes in TIS were also associated with pervasive changes in immune cell density and spatial relationships—in particular, between T cell subsets and antigen presenting cells. We identified an increased density of CD4 + FOXP3 + T cells, CD68 + macrophages and CD68 + CD11c + dendritic cells in response to HDRBT. The only subset change specific to tumor zones was PDL1 - macrophages. While these immune responses were heterogeneous, HDRBT induced significant changes in immune cell associations, including a gained T cell and HMWCK + PDL1 + interaction in tumor zones. Conclusion: In conclusion, we showed HDRBT converted "cold" prostate tumors into more immunologically activated "hot" tissues, with accompanying spatially organized immune infiltrates and signaling changes. Understanding and potentially harnessing these changes will have widespread implications for the future treatment of localized PCa, including rational use of combination radio-immunotherapy.